Barriers to myGAP certification: a study of farmer knowledge, intentions, and challenges in Kelantan, Malaysia / Nor Ashikin Mohd Arifin … [et al.] - Mohd Arifin, Nor Ashikin; Ismail, Nur Amalina; Bakar, Muhammad Aliuddin; Syahlan, Syahrizan; Zulkifli, Farahida (Universiti Teknologi MARA, Sabah, 2024)
myGAP stands as a beacon of excellence in agriculture, aquaculture, and livestock, symbolizing a commitment to environmental stewardship, economic viability, and social responsibility. This certification program guarantees that products meet the highest safety and quality standards. This study embarks on an exploratory journey to understand the depth of adaptation to Malaysian Good Agricultural Practices (myGAP) among the farming communities in Kelantan. The research employs a detailed quantitative methodology to achieve its objectives. The analytical framework includes descriptive analysis, Pearson correlation, and multiple regression. The findings offer significant insights: a considerable proportion of Kelantan farmers deeply understand myGAP, with more than half demonstrating a strong grasp of its principles. Coupled with this awareness is a marked interest in adapting myGAP, primarily motivated by enhancing product safety and quality. However, the path to adaptation is filled with obstacles. Among the various factors considered, such as knowledge, cost constraints, and the role of extension agents, the certification process emerges as the main barrier, underscored by its significant impact. Thus, the study highlights Kelantan farmers' high level of awareness and willingness to adapt to myGAP and points out the crucial adjustments needed to facilitate this process. To enhance accessibility and reduce the complexity for farmers, streamlining the myGAP certification process is recommended. Such simplification could involve reducing paperwork, offering more explicit guidelines, and employing digital platforms to ease the application and monitoring processes.